Identifikasi Potensi Pengembangan Pariwisata Halal di Desa Wisata Lebak Muncang Kabupaten Bandung - Suryana, Marceilla; Utomo, Sherly Raka Siwi (Jurnal Ilmiah Pariwisata, 2020)
The development of halal tourism, is closely related to the number of the world's Muslim population (Muslims) which experienced a significant increase and had an impact on the needs of halal tourism. Lebak Muncang Tourism Village in Ciwidey is one of the tourist villages in Regency of Bandung, that which has quite a lot of tourism potential with the majority of the population being Muslim (Muslim), where the daily activities of the people are influenced by Islamic religious rules (Sharia). If it is related to the tourism industri, Lebak Muncang tourism village has the opportunity to be developed into halal tourism. However, until now, the management of Lebak Muncang tourism village has not been done. This study aims to identify the potential of halal tourism in Lebak Muncang tourism village. This study was analyzed by a qualitative approach with data collection conducted through in-depth interviews, direct observation and literature review, then analyzed by equating the existing conditions with the criteria of halal tourism owned by GMTI and the halal tourism guidance book with the analysis results obtained tourism potential in the village Lebak Muncang Tourism. That is included in criteria and has the potential to be developed into halal tourism.